Evaluasi Kualitas Sedimen Beberapa Tambak Udang Di Kabupaten Tulang Bawang Provinsi Lampung - Supono, Supono (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2015)
Pond bottom management play an important role in the success of shrimp culture. Study on the use of pond bottom pond as an indicator of shrimp pond productivity is still limitted. Shrimp culture has been developing in tulang Bawang Regency, Province of Lampung since early 1990. The waste produced by shrimp culture activity is possible to reduce pond bottom soil quality due to high organic compund and toxic material. The aim of this research was to evaluate the shrimp ponds bottom condition in Tulang Bawang Regency, Province of Lampung. This research was an explorative one. Data collection was done towards 12 shrimp pond units during water preparation period (pre-spreading) with the different locations of each pond from the watergate. The collected data of pond soil qualities were organic matter content, chlorophyll a, cation exchange capacity, oxidation-reduction potential, pH, and soil texture. The research results showed that soil qualities in shrimp ponds in Tulang Bawang Regency were still in range for shrimp culture. In generally, shrimp ponds in the area have soil textute of clay, sandy, and sandy clay.Chlorophyll a content, oxidation reduction potential (ORP) and organic carbon matter content were 21,5 μg/g, 76 mv and 1,26% in average respectively. Meanwhile cation exchange capacity and soil pH were 11,2 me/100g and 6,8 in average.